DIRECTIONS AND PRINCIPLES OF DEVELOPMENT OF THE NATIONAL ECONOMY OF UZBEKISTAN - Anarmatov Jasurbek Jandarbekovich (Galaxy International Interdisciplinary Research Journal, 2023)
In this article, hecitated the principles, directions, and achievements of our country in economic growth with facts and figures. It also details the opinions, analysis, and conclusions of experts in further development of Uzbekistan.